2022
DOI: 10.3389/fsurg.2022.913456
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Bilateral Biportal Endoscopic Open-Door Laminoplasty With the Use of Suture Anchors: A Technical Report and Literature Review

Abstract: BackgroundUnilateral biportal endoscopy (UBE) is a newly developed technique for spine surgery. Owing to the convenience of nerve decompression and compatibility with open surgical instruments under endoscopic guidance, this technique has seen widespread global use. In this study, we first used modified UBE with suture anchor fixation for cervical laminoplasty in a 65-year-old female patient with good clinical outcomes.MethodsWe used bilateral biportal endoscopy (BBE) for cervical laminoplasty with suture anch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Kim reported a UBE technique to decompress central canal stenosis, but the technical requirements were relatively demanding [ 14 ]. The authors not only designed a contralateral “Zhang’s portal” to facilitate single level decompression [ 15 ] but also modified an endoscopic expansive laminoplasty for multisegmental stenosis [ 16 ]. In addition, we attempted UBEL combined with the lateral mass screw fixation technique to treat CS with instability [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim reported a UBE technique to decompress central canal stenosis, but the technical requirements were relatively demanding [ 14 ]. The authors not only designed a contralateral “Zhang’s portal” to facilitate single level decompression [ 15 ] but also modified an endoscopic expansive laminoplasty for multisegmental stenosis [ 16 ]. In addition, we attempted UBEL combined with the lateral mass screw fixation technique to treat CS with instability [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…An independent portal was used for surgical surgery, which effectively broadened the surgical field of vision and made the surgery more flexible. The direction of the portal could be adjusted according to needs, and the scope of surgery was expanded to avoid visual field blindness caused by the obstruction of a single portal [17][18][19]. For cases of ULDH with central canal stenosis, even contralateral nerve root compression, the UBE technique could be used to remove the protruding nucleus pulposus, while the posterior hyperplastic ligamentum flavum and part of the base of the spinous process could be removed to expand the central canal as needed.…”
Section: Clinical Efficacy and Advantages Of Ube Technology In Treati...mentioning
confidence: 99%
“…Recently, studies have described endoscopic surgery with screw fixation. Zhu et al 63,64 attempted the posterior UBE approach for cervical stenosis and performed decompressive laminectomy and unilateral lateral mass screw fixation, and reported that open-door laminoplasty also was possible with UBE. Lvov et al 65 reported endoscope-assisted posterior transarticular standalone screw fixation of C1-2 in traumatic injury patients, and found better pain scale recovery after surgery, less blood loss, and shorter operation time.…”
Section: Cervical Spinementioning
confidence: 99%